Homeostatic-related peptides injected into the rat nucleus accumbens alter palatable eating and impact the binge-like intake of a sweetened fat diet during simultaneous μ-opioid receptor stimulation - Pratt, Wayne E.; Do, Cardinal; Groome, Alexandra M.; Smith, Alana J.; Siegfried, Allison C.; Calafiore, Camryn J. (Frontiers in Neuroscience, 2025)
BackgroundThe nucleus accumbens is central for directing motivated behavior and is a key node in the neural circuitry that promotes eating in response to palatable diets. We examined the impact of intra-accumbens injections of a variety of homeostatic-related peptides (HRPs) on eating elicited by a sweetened fat diet, with or without co-administration of the prophagic mu-opioid agonist [D-Ala2, N-MePhe4, Gly-ol]-enkephalin (DAMGO).MethodsRats received surgical placement of guide cannulas above the anterior medial nucleus accumbens. Non-restricted animals were then accustomed to 2-h daily access to a sweetened fat diet. Palatable eating was examined following intra-accumbens injections of one hypothalamic HRP, alone or with co-infusions of DAMGO.ResultsNucleus accumbens injections of neuropeptide Y (NPY) and Orexin-A significantly increased palatable eating. Cocaine- and amphetamine-related transcript (CART) reduced intake. When rats received co-stimulation of μ-opioid receptors, NPY and DAMGO had a synergistic effect on food intake, whereas Orexin-A initially disrupted eating on the palatable diet and had no additive effect with DAMGO by the end of the session. Neither agouti-related protein (AGRP), melanin concentrating hormone (MCH), alpha-melanocyte stimulating hormone (αMSH), nor the stress-related peptides corticotropin-releasing factor (CRF) or urocortin impacted intake, although MCH and CRF both affected eating in response to mu-opioid receptor stimulation dependent upon the dose.ConclusionThese experiments offer insight into the regulation of hedonically motivated feeding by homeostatic- and stress-related inputs to the nucleus accumbens. This systematic examination suggests that the nucleus accumbens’ role in promoting palatable eating is not independent of the homeostatic signals that reach it from the hypothalamus and other brain regions.